2021
DOI: 10.1093/reseval/rvab007
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between interdisciplinarity and impact: Distinct effects on academic and broader impact

Abstract: Addressing many of the world’s contemporary challenges requires a multifaceted and integrated approach and, in this respect, interdisciplinary research (IDR) is increasingly recognized as central to both academic interests and national science policies. In spite of the growing attention given to IDR, the impact of IDR remains under-investigated. In this study, we analyzed the influence of interdisciplinarity on citation impact (particularly, WoS citation) and broader impact (particularly, PloS usage) at the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Larivière & Gingras (2010) found that the level of interdisciplinarity of articles and their citation rates are not systematically positively correlated. However, a study by Zhang et al (2020c) has shown that higher interdisciplinary publications tend to attract more citations and have higher PLOS usage (Zhang et al, 2021c). In summary, previous studies have obtained diverging results regarding the relationship between the impact and the interdisciplinarity of articles, probably because different indicators and citation windows were used and different disciplines were focused on.…”
Section: Methodsmentioning
confidence: 96%
“…Larivière & Gingras (2010) found that the level of interdisciplinarity of articles and their citation rates are not systematically positively correlated. However, a study by Zhang et al (2020c) has shown that higher interdisciplinary publications tend to attract more citations and have higher PLOS usage (Zhang et al, 2021c). In summary, previous studies have obtained diverging results regarding the relationship between the impact and the interdisciplinarity of articles, probably because different indicators and citation windows were used and different disciplines were focused on.…”
Section: Methodsmentioning
confidence: 96%
“…Larivière and Gingras (2010) found that the level of interdisciplinarity of articles and their citation rates are not systematically positively correlated. However, a study by Zhang et al (2021c) has shown that higher interdisciplinary publications tend to attract more cita-tions and have higher PLoS usage (Zhang et al, 2021c). In summary, previous studies have obtained diverging results regarding the relationship between the impact and the interdisciplinarity of articles, probably because different indicators and citation windows were used and different disciplines were focused on.…”
Section: Methodsmentioning
confidence: 96%
“…Results for the BP tests and GVIF are provided in S7 File . We also compare our results from the log-transformed linear regression model to a negative binomial regression model, which can also be used to model citations as a dependent variable [ 12 , 53 , 56 ]. The results are similar and are discussed in S8 File .…”
Section: Methodsmentioning
confidence: 99%
“…Given the “high risk, high gain” [ 14 ] nature of IDR, it is unsurprising that previous research found mixed results on its association with research impact. On the one hand, IDR plays an important role in the emergence of high impact research [ 13 , 15 , 53 ], although at the cost of productivity [ 20 ]. On the other hand, IDR is found to be detrimental for research impact.…”
Section: Related Workmentioning
confidence: 99%